2016
DOI: 10.1371/journal.pone.0167118
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Wave Elastography for the Differential Diagnosis of Breast Papillary Lesions

Abstract: ObjectiveTo evaluate the diagnostic performance of shear-wave elastography (SWE) for the differential diagnosis of breast papillary lesions.MethodsThis study was an institutional review board-approved retrospective study, with a waiver of informed consent. A total of 79 breast papillary lesions in 71 consecutive women underwent ultrasound and SWE prior to biopsy. Ultrasound features and quantitative SWE parameters were recorded for each lesion. All lesions were surgically excised or excised using an ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As shown in figure 1, a total of 169 studies were found after initial search. Finally, 14 studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23] were included in our diagnostic meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…As shown in figure 1, a total of 169 studies were found after initial search. Finally, 14 studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23] were included in our diagnostic meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%